2012
DOI: 10.1089/dna.2011.1346
|View full text |Cite
|
Sign up to set email alerts
|

Search for Variation in the Ovine KAP7-1 and KAP8-1 Genes Using Polymerase Chain Reaction–Single-Stranded Conformational Polymorphism Screening

Abstract: Keratins and keratin-associated proteins (KAPs) are large heterogeneous groups of proteins that constitute about 90% of the wool fiber. The genes encoding the high glycine-tyrosine (HGT) KAPs are the first sub-group of KAP genes expressed in the wool follicle and just after expression of the keratin genes. Little is known about variation in these genes, which led us to investigate two HGT-KAP genes, KRTAP7-1 and KRTAP8-1. Polymerase chain reaction-single-stranded conformational polymorphism analysis was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 16 publications
(20 reference statements)
2
29
0
Order By: Relevance
“…This is consistent with the finding of sequence variation in other ovine KRTAPs (Gong et al 2012a; Gong et al 2011a; Gong et al 2011b; Gong et al 2012b; Gong et al 2012c; Zhou et al 2012). However, in contrast to other KRTAPs , the variation found in ovine KRTAP8-2 was not within the coding region, but instead located near the TATA box.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with the finding of sequence variation in other ovine KRTAPs (Gong et al 2012a; Gong et al 2011a; Gong et al 2011b; Gong et al 2012b; Gong et al 2012c; Zhou et al 2012). However, in contrast to other KRTAPs , the variation found in ovine KRTAP8-2 was not within the coding region, but instead located near the TATA box.…”
Section: Discussionsupporting
confidence: 91%
“…Only one member of the KAP8 gene family has been identified to date (McLaren et al, 1997;Gong et al, 2012). Previous studies have demonstrated abundant variations in the KAP8 gene.…”
Section: Kap8 Gene Polymorphismsmentioning
confidence: 99%
“…Wood et al (1992) reported 11 KAP8 alleles in a group of 33 unrelated sheep from various breeds based on dinucleotide length variation in PCR amplification of the 5'-flanking region of the gene. More recently, five different nucleic acid sequences were found in the CDS region of the KAP8 gene (Gong et al, 2012).…”
Section: Kap8 Gene Polymorphismsmentioning
confidence: 99%
“… 1 HS: ≤30 mol % cysteine; UHS: >30 mol % cysteine; HGT: 35-60 mol % of glycine and tyrosine. 2 Membership is based on the identification of the gene, and not the protein. 3 Numbers after “+” represent pseudogenes, and numbers of family members having genetic variation reported are shown in the brackets. 4 Superscript letters indicate the references from which the genetic information was derived: a 35, b 7, c 29, d 40, e 41, f 42, g 43, h 30, i 44, j 3, k 36, l 4, m 45, n 37, o 26, p 25, q 5, r 23, s 6, t 46, u 38 and v 39. 5 While there are currently only three genes reported in the literature for KAP1, there are four known protein sequences. 6 No ovine genes have been identified, despite three protein sequences having been reported 10,47.…”
Section: Figmentioning
confidence: 99%